Association of dietary intake of polyphenols, lignans, and phytosterols with immune-stimulating microbiota and COVID-19 risk in a group of Polish men and women - Micek, Agnieszka; Bolesławska, Izabela; Jagielski, Paweł; Konopka, Kamil; Waśkiewicz, Anna; Witkowska, Anna Maria; Przysławski, Juliusz; Godos, Justyna (Frontiers in Nutrition, 2023)
Objectives: Devastating consequences of COVID-19 disease enhanced the role of promoting prevention-focused practices. Among targeted efforts, diet is regarded as one of the potential factors which can affect immune function and optimal nutrition is postulated as the method of augmentation of people's viral resistance. As epidemiological evidence is scarce, the present study aimed to explore the association between dietary intake of total polyphenols, lignans and plant sterols and the abundance of immunomodulatory gut microbiota such as Enterococcus spp. and Escherichia coli and the risk of developing COVID-19 disease. Methods: Demographic data, dietary habits, physical activity as well as the composition of body and gut microbiota were analyzed in a sample of 95 young healthy individuals. Dietary polyphenol, lignan and plant sterol intakes have been retrieved based on the amount of food consumed by the participants, the phytochemical content was assessed in laboratory analysis and using available databases.Results: For all investigated polyphenols and phytosterols, except campesterol, every unit increase in the tertile of intake category was associated with a decrease in the odds of contracting COVID-19. The risk reduction ranged from several dozen percent to seventy percent, depending on the individual plant-based chemical, and in most cases, it was statistically significant after controlling for basic covariates it was statistically significant for secoisolariciresinol (OR = 0.28, 95% CI: 0.11-0.61), total phytosterols (OR = 0.47, 95% CI: 0.22-0.95) and for stigmasterols (OR = 0.34, 95% CI: 0.14-0.72). We found an direct inverse association between increased β-sitosterol intake and phytosterols in total and the occurrence of normal amounts of Escherichia coli in stool samples outside reference values, with 72% (OR = 0.28, 95% CI: 0.08-0.86) and 66% (OR = 0.34, 95% CI: 0.10-1.08) reduced odds of abnormal level of bacteria for higher compared with the lowest tertile of phytochemical consumption. Additionally, there was a trend of more frequent presence of Enterococcus spp. at relevant level in people with a higher intake of lariciresinol. Conclusions: The beneficial effects of polyphenols and phytosterols should be emphasized and these plant-based compounds should be regarded in the context of their utility as antiviral agents preventing influenza-type infections.